Talent policy in the public sector: Comparative analysis of the US and China and lessons learned for Vietnam - võ anh nguyễn (Revista Jurídica Portucalense)
This article provides a comparative analysis of public sector talent policies in the United States (US) and China, focusing on extracting lessons for Vietnam. Utilizing a qualitative comparative methodology based on legal documents, policy frameworks, academic literature, and government reports, the study examines four key aspects: talent recruitment; planning and appointment; training; and treatment regimes. The analysis highlights significant differences stemming from contrasting political systems and strategic priorities, such as China's centralized, Party-influenced approach versus the US's decentralized, merit-focused system with strong non-wage benefits. While both nations prioritize talent, their strategies diverge, particularly in balancing political loyalty with meritocracy and central control with agency autonomy. The findings reveal specific legal and policy mechanisms influencing talent attraction and retention. Based on this comparison, the article concludes with actionable recommendations for Vietnam, emphasizing the need for a unified national strategy, transparent merit-based processes adapted to Vietnam's context, competitive compensation, and clear career pathways, referencing specific areas within Vietnam's existing legal framework for potential reform.